Antifungal drugs: Targeting histone acetylation - Harrison, Charlotte
The fungal pathogen Candida albicans causes serious infections in immunocompromised individuals, and although treatment is possible using azole or echinocandin drugs, their efficacy can be compromised by the emergence of drug-resistant strains. Writing in Nature Medicine, Wurtele and colleagues show that fungal enzymes that regulate histone acetylation - specifically the acetylation of lysine 56 on histone H3 (H3K56ac)- could be new targets for the treatment of C. albicans
Keywords: CANDIDA ALBICANS; FUNGALS; PATHOGENS